ETNOBOTANI TUMBUHAN OBAT DI DUSUN SERAMBAI KECAMATAN KEMBAYAN KABUPATEN SANGGAU KALIMANTAN BARAT - Sari, Rizki Yunita; Wardenaar, Evy; hati, Mufli (Universitas Tanjungpura, 2014)
The study was conducted in serambai village, Sub-District of kembayan, Sanggau. The purpose of this study is to determine the types of plants, particularly certain parts of plants that can be used for treatment of various diseases and to know the way of processing by Malay and Dayak communities in Serambai village. The results of this study are expected to provide information to society about the benefits of some medicinal plant species that exist in the village of Serambai and invite surrounding people to preserve and cultivate such medicinal plants for the benefit of general public in future. Based on the results of research on some medicinal plants used by the Malays and Dayaks in surrounding village of Serambai, there are 51 species of medicinal plants that belong to 35 families. Surrounding communities usually cultivate such medicinal plants traditionally based on habits and experiences. Based on the growth rate, the percentage of trees that were used by people in Serambai village amounted to 33,33% while based on the type of single herba, 78,43% was benefited. Leaves were part of plant that often usedby villagers. Its amount was 39,62%. For processing, boiling is a favorite pattern that was often applied by people with percentage amount of 58,50%. Having processed traditionally, 59,26% of people taking it by mouth and 72,22% of local people exploited the properties of the leaves to treat internal illnesses. Keywords : Ethnobotany , medicinal plants , people , Sanggau